PENERAPAN PENDEKATAN WHOLE LANGUAGE DALAM MENINGKATKAN KEMAMPUAN MEMBACA DALAM TEKS BERBAHASA INGGRIS - Lia Amelia (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2024)
One of the most influential fields in global communication is language. Language is a means of communication exchange that can cross between countries. Learning English is a subject that is considered difficult because English is not the mother tongue or national language used every day, this causes boredom. This type of research is conceptual research. By implementing the Whole Language approach, it is easier for students to read English texts. The aim of the research is to describe the application of the whole language approach in learning English. The results of this research are that the whole language approach in language learning is integrated or cannot be separated and each learning approach has advantages and disadvantages, including the whole language approach. However, this deficiency can certainly be overcome when educators can understand the components or how to apply a whole language approach.